2020
DOI: 10.3390/pharmaceutics12121132
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Nanoparticles as Formulative Strategy to Increase Oral Permeation of a Molecule Active in Multidrug-Resistant Tuberculosis Management

Abstract: The role of mycobacterial efflux pumps in drug-resistant tuberculosis has been widely reported. Recently, a new compound, named SS13, has been synthesized, and its activity as a potential efflux inhibitor has been demonstrated. In this work, the chemical–physical properties of the SS13 were investigated; furthermore, a formulative study aimed to develop a formulation suitable for oral administration was performed. SS13 shows nonintrinsic antitubercular activity, but it increases the antitubercular activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The above results demonstrated that QT–NSSPE could significantly improve the oral bioavailability of QT, which may be responsible for the follow reasons: (a) Most of QT in QT–NSSPE was in the form of nanocrystals, the smaller size and larger surface area of nanocrystals lead to higher dissolution rate, hence increasing the oral bioavailability of poorly water-soluble drugs [ 52 , 53 ]. (b) With an oily inner core of emulsion droplets, QT–NSSPE had partially characteristic of type I lipid formulations [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The above results demonstrated that QT–NSSPE could significantly improve the oral bioavailability of QT, which may be responsible for the follow reasons: (a) Most of QT in QT–NSSPE was in the form of nanocrystals, the smaller size and larger surface area of nanocrystals lead to higher dissolution rate, hence increasing the oral bioavailability of poorly water-soluble drugs [ 52 , 53 ]. (b) With an oily inner core of emulsion droplets, QT–NSSPE had partially characteristic of type I lipid formulations [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alongside this, an untreated intestinal mucosa was used as a control. The intestine sections were placed on a 12-well cell culture plate that had been suitably modified (project INCREASE SARDINIA 2016-17, protocol number 31351, University of Sassari) [ 31 ] and previously filled with PBS (pH 6.8). An exact amount of sample (200 µl of F-SLN and fluorescein solution, corresponding to 0.1 mg of fluorescein) was placed on the mucosal surface of the intestine segments, and the plate was positioned in the incubator shaker apparatus at 25 °C and 150 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…The NP-C spectrum exhibits similar bands to NP-Cb, and it does not show the characteristic peak of CAT at 2566 cm −1 which is, however, visible in the physical mixture. This absence could be ascribed to the loading of CAT in the polymer matrix [37] or molecular interactions with the NP components that are not developed in the physical mixture and could be responsible for the shoulder at 2600-2450 cm −1 (Figure 3). In the physical mixture, the peak at 1747 cm −1 related to the carboxylic group of CAT is also evident.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 99%